2007
DOI: 10.1002/chem.200601253
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Interaction in an Asymmetric End‐to‐End Azido Double‐Bridged Copper(II) Dinuclear Complex: A Combined Structure, Magnetic, Polarized Neutron Diffraction and Theoretical Study

Abstract: A new end-to-end azido double-bridged copper(II) complex [Cu(2)L(2)(N(3))2] (1) was synthesized and characterized (L=1,1,1-trifluoro-7-(dimethylamino)-4-methyl-5-aza-3-hepten-2-onato). Despite the rather long Cu-Cu distance (5.105(1) A), the magnetic interaction is ferromagnetic with J= +16 cm(-1) (H=-JS(1)S(2)), a value that has been confirmed by DFT and high-level correlated ab initio calculations. The spin distribution was studied by using the results from polarized neutron diffraction. This is the first su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 65 publications
2
52
0
Order By: Relevance
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 90%
See 1 more Smart Citation
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 90%
“…So far, the DDCI approach has been extensively employed in the evaluation of J in molecular and solid state magnetic materials with a remarkable good agreement with experiment. [20][21][22][23][24][25][26][27][28][29][30][31][32] Some years ago we took benefit of this methodology to analyze in depth the physical contributions to the magnetic coupling on a series of binuclear Cu ͑II͒ complexes. 33 The use of the DDCI strategy allows not only to obtain quite accurate J values but also to analyze the various physical effects by generating CI spaces of increasing lengths that include different types of determinants.…”
Section: Introductionmentioning
confidence: 99%
“…The rational design and synthesis of polynuclear complexes, aiming at understanding the factors that govern the final structures, are of continuing interest in coordination and structural chemistry. As is well known, the azido ligand can link two or more metal atoms through the l 1,1 -(end-on, EO), l 1,3 -(end-to-end, EE), l 1,1,3 -, and many other modes, yielding various polynuclear complexes that are difficult to achieve with other bridging ligands [4][5][6]. It seems that the azido ligands readily adopt l 1,1 -and l 1,3 -bridging modes in the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…HF-EPR measurements should give information on the sign and magnitude of the anisotropy [17] while the polarized neutron diffraction has proven to be relevant to obtain information on the spin delocalization. [18][19][20][21][22][23] We also performed theoretical studies of the magnetic exchange coupling as well as spin-density calculations using the density functional theory (DFT) formalism. Hence, recently some of us have studied the magnetism of several tetranuclear Cu II complexes (Cu 4 ) with cubane-like structures.…”
mentioning
confidence: 99%